Machining of nickel alloy 242 with cubic boron nitride tools - Habeeb H.H.; Kadirgama K.; Noor M.M.; Rahman M.M.; Mohammad B.; Bakar R.A.; Abouel Hossein K.A. (Asian Network for Scientific Information, 2023)
This study discusses the development of first and second order of surface roughness prediction model when machining Haynes 242 alloy with Cubic Boron Nitride (CBN) at dry condition. The relationship between the cutting parameters (cutting speed, axial depth and feedrate) with surface roughness are discussed. Response Surface Method (RSM) has been selected to optimize the cutting parameters and reduce the number of experiments. Surface roughness obtained in these experiments ranged from 0.052-0.08 ?m, which consider as an extremely fine finish. Increase in cutting speed from 70 to 300 m min-1, the roughness getting finer. On other hand, increase in feedrate (0.1 to 0.3 mm tooth-1) and axial depth (0.025 to 0.075 mm) surface roughness become rougher. 2010 Asian Network for Scientific Information.